Wetlands of Sub-Saharan Africa: distribution and contribution of agriculture to livelihoods - Rebelo, Lisa-Maria; McCartney, Matthew P.; Finlayson, C. Max (Springer, 2010)
Wetlands contribute in diverse ways to the livelihoods of millions of people in Sub-Saharan Africa. In many places they are inextricably linked to cropping and livestock management systems. At the same time, increasing population in conjunction with efforts to increase food security is escalating pressure to expand agriculture within wetlands. The environmental impact of wetland agriculture can, however, have profound social and economic repercussions for people dependent on ecosystem services other than those provided directly by agriculture. Currently, the basis for making decisions about the extent to which wetlands can be sustainably used for agriculture is weak. This paper provides an overview of wetland distribution, type and condition across Sub-Saharan Africa. Findings from an investigation of wetland use conducted in Tanzania are presented. These highlight the reliance of communities on both wetland agriculture and natural resources, and show that the nature of household dependence varies significantly from place to place and as socio-economic status changes. Consequently, incentives to manage wetland resources will differ markedly, not only from one location to another, but also across socio-economic groups within the same community. This complexity highlights the need for critical analysis of the social and economic factors that underpin the dynamics of wetland resource use in the development of sustainable management plans.